DEVELOPMENT AND VALIDATION OF DOUBLE DIVISOR RATIO SPECTRA DERIVATIVE SPECTROPHOTOMETRY METHOD FOR TERNARY MIXTURE OF GUAIFENESIN, DEXTROMETHORPHAN HBR, AND DIPHENHYDRAMINE HCL IN TABLET DOSAGE FORM - Adriani, Fitria; BACHRI, MUCHLISYAM; Sinaga, Siti Morin (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: This study aimed to develop spectrophotometry method by double divisor ratio spectra derivative to determine the levels of guaifenesin (GUA), dextromethorphan hydrobromide (DMP), and diphenhydramine hydrochloride (DPH) in tablet dosage form using ethanol as solvent. Methods: The method is based on the use of the coincident spectra of the derivative of the ratio spectra obtained using a double divisor (sum of two spectra) and measuring at either the maximum or minimum wavelengths. Then, the method was applied to determine the levels of GUA, DMP, and DPH in tablet dosage form. Results: The application of double divisor ratio spectra derivative spectrophotometry method for the determination of GUA, DMP, and DPH was performed on the first derivative at Î”Î» 2 (Î» 280.0 nm, Î» 286.1 nm, and 260.2 nm, respectively). The selection of wavelengths based on wavelengths gives the best result. The mean % recoveries were found to be in 100.60%, 99.95%, and 101.74% for GUA, DMP, and DPH, respectively. Conclusion: The method is successfully applied to analyze GUA, DMP, and DPH in pharmaceutical formulation with no interference from excipients as indicated by the recovery study. All validation parameters were within the acceptable range.